Potential of Microbial Isolates from Indonesia in Producing Antimicrobial Compounds: A Review - Geraldi, Almando; Wijaya, Nabilla Hapsari; Clement, Christopher; Hajar, Versa Rachmania (Universitas Airlangga, 2023)
Indonesia, as a megabiodiverse country, possesses a wealth of beneficial microorganisms, including bacteria and fungi capable of producing antimicrobial compounds. Over the past decade, extensive research has been conducted in Indonesia to explore and screen the antimicrobial activities of bacteria and fungi. These microorganisms have been isolated from various ecosystems, such as terrestrial, maritime, extreme environments like hot springs and sand dunes, as well as from animals and plants hosts. Most studies have focused on the antimicrobial activity of crude metabolite extracts, which demonstrate inhibitory effects against clinically significant pathogens, including Methicillin-resistant Staphylococcus aureus, multidrug-resistant Escherichia coli, and Salmonella typhi. This review systematically synthesizes findings from peer-reviewed literature, detailing isolation strategies, antimicrobial screening techniques, and the bioactivities reported. By consolidating current knowledge, it aims to elucidate the potential of Indonesia’s microbial resources for developing novel antimicrobial agents and promoting their sustainable exploitation within the context of global health challenges.